Molecular Epidemiology of Hypervirulent Carbapenemase-Producing Klebsiella pneumoniae - Hu, Dakang; Li, Yuming; Ren, Ping; Tian, Dongxing; Chen, Wenjie; Fu, Pan; Wang, Weiwen; Li, Xiaobin; Jiang, Xiaofei (Frontiers in Cellular and Infection Microbiology, 2021)
Objective To investigate the overall distributions of key virulence genes in Klebsiella pneumoniae, especially the hypervirulent blaKPC-positive K. pneumoniae (Hv-blaKPC(+)-KP). Methods Totally 521 genomes of K. pneumoniae from GenBank) were collected and analyzed. Multilocus sequence typing, molecular serotyping, antibiotic-resistance, virulence genes and plasmid replicon typing were investigated. Results Positive rates of virulence genes highly varied, ranging from 2.9% (c-rmpA/A2) to 99.6% (entB). Totally 207 strains presented positive fimH, mrkD, entB and wzi and 190 showed positive fimH, mrkD, entB, irp2 and wzi, which were the 2 primary modes. Totally 94, 165 and 29 strains were denoted as hypervirulent K. pneumoniae (HvKP), blaKPC(+)-KP and Hv-blaKPC(+)-KP. ST11 accounted for 17 among the 29 Hv-blaKPC(+)-KP strains; Genes iucA, p-rmpA2 and p-rmpA were positive in 28, 26 and 18 Hv-blaKPC(+)-KP strains respectively. Among the 29 Hv-blaKPC(+)-KP strains exhibiting 4 clusters from GenBank, IncHI1B plasmids carrying virulence genes and IncFII ones with blaKPC were responsible for both 23 strains respectively. Conclusions Positive rates of virulence genes vary remarkably in K. pneumoniae. Genes iucA, p-rmpA2 and p-rmpA were primary ones inducing Hv-blaKPC(+)-KP. IncHI1B plasmids carrying virulence genes and IncFII ones with blaKPC constitute the primary combination responsible for Hv-blaKPC(+)-KP. The making of Hv-blaKPC(+)-KP is mostly via blaKPC(+)-KP acquiring another plasmid harboring virulence genes.